Challenges Faced by Nursing Profession in Saudi Arabia (The Review of Diabetic Studies, 2024)
Saudi Arabia is currently dealing with a severe nursing shortage and a significant reliance on foreign nurses, which creates particular difficulties. There is a scarcity of nurses in the workforce on a global scale. The goal of this integrative literature review is to identify some of the distinct social and cultural factors that contribute to the worldwide nursing workforce deficit in addition to the dominant trends. The rationale behind this strategy was the recognition that a persistently high reliance on an international workforce has dangers and could lead to a significant workforce crisis in the event that a significant number of foreign nurses left the nation. This present study evaluates the scenario in terms of studies conducted in the time frame of 2010 to 2023. The mode of study is exploratory and takes the reference from various other sources as well.